The role of cytokines in pathogenesis of periodontal and periapical lesions - M. Abdolahi nejad; A. Masod (Tehran University of Medical Sciences, 1993)
Cytokines are glycoproteins produced  specifically by lymphocytes, macrophages, monocytes and many other cells. In fact, They act nonspecifically. Cytokines are not immunoglubolins and unlike them, have not high molecular weight. They regulate immuneresponse as well as in diagnosis and treatment of diseases. Cytokines role  in periodontal diseases as well as identifying them in the pathogenesis of some dental and oral diseases and bone loss process is an important issue in dentistry. Hence, this article presents cytokine's role and developments of immunology science in dentistry.